Exploring a Whole Understanding of Public Policy Evaluation - Dorthea Renyaan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This article aims to analyze the dichotomies and intersections of public interest, evaluation studies, and policy changes, so as to provide policy evaluators with substantial understanding at both a conceptual and a comprehensive practice level. This research uses a type of research in the form of library research. Sources of data obtained from relevant literature, such as books, journals, or scientific articles related to the selected topic. The results of the research in this article show that the views of experts are focused on how the dynamics of policy issues vary. The main challenges in evaluation studies include the uncertainty of policy objectives, causality relationships, spread of policy influence, difficulty in obtaining data, and official resistance. Policy changes influenced by proposals for new policies may overlap, at least in part, with existing programs. Policy may create conditions that require change because of inadequate or conflicting effects.